1999
DOI: 10.1093/ageing/28.4.367
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between Helicobacter pylori infection and extracardiac atherosclerosis in dyspeptic elderly subjects

Abstract: Background: there are conflicting data on the association between Helicobacter pylori (HP) infection and cardiovascular diseases. Aim: to determine if there is an association between gastric HP infection and atherosclerosis of cerebral or peripheral arteries in elderly subjects. Methods: 90 dyspeptic elderly subjects had upper gastro-intestinal endoscopy and the gastroduodenal pathology was identified. HP infection was confirmed by gastric histology and the rapid urease test. Vascular ultrasonography of extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
1
8
0
1
Order By: Relevance
“…This outcome reinforces the emerging evidence that gastric Helicobacter infection most likely does not exacerbate or accelerate atherosclerotic lesion development (6,33,36).…”
Section: Discussionsupporting
confidence: 83%
“…This outcome reinforces the emerging evidence that gastric Helicobacter infection most likely does not exacerbate or accelerate atherosclerotic lesion development (6,33,36).…”
Section: Discussionsupporting
confidence: 83%
“…The few studies previously performed in elderly populations failed to find any association between H. pylori infection and coronary heart disease [26] or extracardiac atherosclerosis [27]. However, a study from Japan reported that mean serum levels of high‐density lipoprotein cholesterol (HDLC) were significantly lower in H. pylori ‐positive than in H. pylori ‐negative subjects.…”
Section: Indications For Treatment Of the Elderlymentioning
confidence: 99%
“…A scientific debate has arisen about the possible association of H. pylori infection with extradigestive diseases, principally cardiovascular diseases, but also liver and biliary tract diseases, skin diseases, iron deficiency and pernicious anaemia 37 . The few studies performed in elderly populations failed to find any association between H. pylori infection and coronary heart disease 38 , 39 or extracardiac atherosclerosis 40 . To date, the presence of extradigestive diseases in subjects is not an indication for the testing or treatment of H. pylori .…”
Section: Indications For Treatment In the Elderlymentioning
confidence: 99%
“…37 The few studies performed in elderly populations failed to find any association between H. pylori infection and coronary heart disease 38,39 or extracardiac atherosclerosis. 40 To date, the presence of extradigestive diseases in subjects is not an indication for the testing or treatment of H. pylori.…”
Section: Extradigestive Diseasesmentioning
confidence: 99%